2022
DOI: 10.2196/32331
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Serious Games for Alleviating Depression: Systematic Review and Meta-analysis

Abstract: Background Depression is a common mental disorder characterized by disturbances in mood, thoughts, or behaviors. Serious games, which are games that have a purpose other than entertainment, have been used as a nonpharmacological therapeutic intervention for depression. Previous systematic reviews have summarized evidence of effectiveness of serious games in reducing depression symptoms; however, they are limited by design and methodological shortcomings. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 70 publications
(138 reference statements)
5
29
0
1
Order By: Relevance
“…This finding is consistent with that of a previous review [ 16 , 62 ]. Specifically, a meta-analysis of 8 studies showed a statistically significant difference ( P =.004) in depression levels between the exergames group and the control group.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This finding is consistent with that of a previous review [ 16 , 62 ]. Specifically, a meta-analysis of 8 studies showed a statistically significant difference ( P =.004) in depression levels between the exergames group and the control group.…”
Section: Discussionsupporting
confidence: 94%
“…This indicates that conventional exercises are at least as effective as conventional exercises. Our findings are similar to those of previous reviews [ 16 , 62 ]. Specifically, a meta-analysis of 5 RCTs showed no statistically significant difference ( P =.81) in anxiety levels between the exergames group and the usual care group (ie, conventional exercises) [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Serious games exist in a variety of formats based on the therapeutic modality, including (1) cognitive training games that aim to maintain or improve users’ cognitive functions, such as working memory and attention; (2) exergames, or video games that entail physical exercises (eg, balance exercises) as part of the intended gameplay; (3) computerized cognitive behavioral therapy (CBT) games, which are video games that provide CBT for the users; and (4) biofeedback games, which are video games that utilize electrical sensors attached to the participant to receive information about the participant’s body state (eg, electrocardiogram sensors) and seek to influence some of the player body’s functions (eg, heart rate). Previous systematic reviews have shown that serious games have the potential to prevent or alleviate mental disorders such as depression [ 14 ] and anxiety [ 15 ]. Further, the literature suggests that serious games can be a good mental stimulant and improve brain health through the use of memory, visualization, and motor skills [ 16 ].…”
Section: Introductionmentioning
confidence: 99%